2019
DOI: 10.1002/jmv.25398
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in IFIH1 and DDX58 influence hepatitis C virus clearance in Chinese Han population

Abstract: Aims To investigate the association between two RIG‐I‐like receptor gene polymorphisms and hepatitis C virus (HCV) infection in Chinese Han population. Methods The current study genotyped two selected SNPs (IFIH1 rs3747517 and DDX58 rs9695310) using TaqMan allelic discrimination assay to assess their association with the susceptibility and clinical outcome of HCV infection among 3065 participants (1545 non‐HCV infection individuals, 568 spontaneous HCV clearance cases, and 952 persistent infection patients). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Interestingly, a prior study showed that IFIH1 is important for immune responses to Candida fungal infections ( Jaeger et al, 2015 ). In addition, prior studies have associated IFIH1 (rs3747517) and UBE2L3 with an inability to clear hepatitis viruses, leading to chronic infection and increased inflammatory states ( Liu et al, 2018 ; Zhu et al, 2019 ; Yao et al, 2021 ). IFIH1 encodes a retinoic acid-inducible gene I (RIG-I)-like receptor that can sense viral RNA in order to establish a proper antiviral host response.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a prior study showed that IFIH1 is important for immune responses to Candida fungal infections ( Jaeger et al, 2015 ). In addition, prior studies have associated IFIH1 (rs3747517) and UBE2L3 with an inability to clear hepatitis viruses, leading to chronic infection and increased inflammatory states ( Liu et al, 2018 ; Zhu et al, 2019 ; Yao et al, 2021 ). IFIH1 encodes a retinoic acid-inducible gene I (RIG-I)-like receptor that can sense viral RNA in order to establish a proper antiviral host response.…”
Section: Discussionmentioning
confidence: 99%
“…There are also correlations with viral infections, such as COVID-19, WNV and EV71. IFIH1 rs9596310 is a risk factor for chronic hepatitis C virus (HCV) infection [ 50 ]. Both EV71 and HCV are positive single-stranded RNA viruses that may cause similar immune responses in the host.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, rs3747517 (H843R), another SNP found in the IFIH1 gene, is a missense variant located at exon 13 of IFIH1 . 42 In humans, the variant of the IFIH1 gene that encodes the H843R polymorphism has been associated with different susceptibilities to multiple viral infections and autoimmune diseases, such as type I diabetes mellitus (T1DM), 43 chronic viral hepatitis, 44 systemic lupus erythematosus, 45 and psoriatic arthritis. 46 In the present study, significant associations were observed between IFIH1 H843R alleles and vitiligo susceptibility.…”
Section: Discussionmentioning
confidence: 99%